Decadal Strengthening of Interior Flow of North Atlantic Deep Water Observed by GRACE Satellites. Issue 11 (31st October 2020) - Koelling, Jannes; Send, Uwe; Lankhorst, Matthias
Abstract: The Gravity Recovery and Climate Experiment (GRACE) satellite mission provides information on changes to the Earth's gravity field, including ocean mass. Long‐term trends in GRACE data are often considered unreliable due to uncertainties in the corrections made to calculate ocean mass from the raw measurements. Here, we use an independent estimate of ocean mass from satellite altimetry and in situ density data from five mooring sites and repeat hydrography to validate trends in GRACE over the North Atlantic, finding substantial agreement between the methods. The root‐mean‐square difference between ocean mass changes calculated with this method from the mooring data and those measured by GRACE is 3.5 mm per decade, much lower than the mean signal of 15.6 ± 1.8 mm per decade for GRACE and 17.8 ± 5.2 mm per decade for the altimetry‐mooring estimate. The GRACE ocean mass data are then used to study the change in the deep circulation of the North Atlantic between the 1 April 2002 to 31 March 2009 and 1 April 2010 to 31 March 2017 periods, revealing a large‐scale anticyclonic circulation anomaly off the North American coast. The change is associated with an increase of 13.9 ± 3.3 Sv (1 Sv = 10 6 m 3 s −1 ) of southward North Atlantic Deep Water flow in the interior between 30°N and 40°N, largely balanced by a northward anomaly of 10.7 ± 3.3 Sv for the boundary circulation. This implies an increased importance of interior pathways compared to the Deep Western Boundary Current for the spreading of North Atlantic Deep Water, which constitutes the lower limb of the Atlantic Meridional Overturning Circulation. Plain Language Summary: The Gravity Recovery and Climate Experiment (GRACE) satellites measure the Earth's gravity field, which can be used to study ocean currents. In this study, we validate long‐term trends in the data using independent ocean measurements to confirm that they reflect real changes in the ocean. In the Atlantic Ocean, North Atlantic Deep Water flows southward from its formation region near Greenland, spreading throughout the ocean basin. The flow of North Atlantic Deep Water is a crucial part of Earth's climate system, making it an important process to understand. Most of the water spreads southward in the so‐called Deep Western Boundary Current along the continental shelves of North America, but there is also a significant flow further offshore in the interior of the basin. We use the GRACE data to measure changes to these two pathways between the 2002–2009 and 2010–2017 periods. The results show that southward flow in the interior has strengthened during this time, with opposite changes near the continent. This marks a significant change to how this water spreads from the formation region. Key Points: GRACE ocean mass trends are validated using mooring and altimetry data Changes reveal decadal variability in the deep circulation of the North Atlantic ocean Flow of North Atlantic Deep Water in the interior strengthened compared to the boundary circulation